Blocker’s activity at men’s european beach volleyball university championship (Actividad de los bloqueadores durante el Campeonato de Europa Universitario de vóley playa) - Jimenez-Olmedo, Jose Manuel; Penichet-Tomas, Alfonso (Retos, 2017)
In this paper, we present a study of blocker’s activity in university beach volleyball players. A total of n=1166 blocking actions were analyzed from 24 European men's teams at the Ninth European Beach Volleyball Championship EUSA GAMES. The analysis of the videos was carried out using the free software program LongoMatch v.0.27. Statistical significance of the comparison of systems was calculated using the Z test to compare proportions. Results showed that blockaders do not have a leading role in the Direct Intervention (DI) of the ball (37%, p